2015
DOI: 10.1063/1.4915128
|View full text |Cite
|
Sign up to set email alerts
|

Application of UV photoluminescence imaging spectroscopy for stacking faults identification on thick, lightly n-type doped, 4°-off 4H-SiC epilayers

Abstract: This paper deals with the description and the application of an original photoluminescence (PL) imaging technique on thick, lighly n-type doped 4H-SiC epilayers for in-grown stacking fault (SF) identification. This technique, call “photoluminescence imaging spectroscopy” (PLIS), compares different PL imaging pictures in order to create a new picture which displays the location and an approximation of the maximum photoemission wavelength of SFs at room temperature. Five types of SF have been detected and identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…defects which mostly show luminescence from 540 to 740 nm. Varying emission of stacking faults is also described in literature [4]. Generally, our UV-PL images of CVD-grown SiC epilayers are of better quality than UV-PL of PVT-grown SiC substrates.…”
Section: Resultssupporting
confidence: 64%
“…defects which mostly show luminescence from 540 to 740 nm. Varying emission of stacking faults is also described in literature [4]. Generally, our UV-PL images of CVD-grown SiC epilayers are of better quality than UV-PL of PVT-grown SiC substrates.…”
Section: Resultssupporting
confidence: 64%
“…1(a)] is likely an extrinsic Frank-type SF or a single Shockley SF, based on the range of wavelength emissions. 6 However, SF2 [the bright SF in Figs. 1(b)-1(e)] seems to have a broad emission, covering the range of 450-500 nm.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis suggested that a triple Shockley SF or an intrinsic Frank-type SF was the most probable option. 6 It is difficult to distinguish between these two SFs due to the similarity in their emission ranges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 . Photoluminescence (PL) imaging spectroscopy is a useful method to detect defects in SiC wafers, as defects such as stacking faults will have a different spectral PL profile than high quality SiC material 3 . In this way, through a raster scanning process, PL has been demonstrated as an imaging method, with a combination of different spectral bandpass filters or spectroscopy instruments, to isolate and image specific defects in SiC wafers 4,5 .…”
Section: Introductionmentioning
confidence: 99%